A Review and Meta-Analysis of Influenza Interactome Studies - Chua, Sonja Courtney Jun Hui; Cui, Jianzhou; Engelberg, David; Lim, Lina Hsiu Kim (Frontiers in Microbiology, 2022)
Annually, the influenza virus causes 500,000 deaths worldwide. Influenza -associated mortality and morbidity is especially high amongst the elderly, children and patients with chronic diseases. While there are antivirals available against influenza such as neuraminidase inhibitors and adamantanes, there is growing resistance against these drugs and there are no effective drugs against influenza. Thus, there is a need for novel antivirals for resistant influenza strains. Host-directed therapies are a potential strategy for influenza as host processes are conserved and are less prone mutations as compared to virus-directed therapies. A literature search was performed for papers that performed viral host-interaction screens and the Reactome pathway database was used for the bioinformatics analysis. A total of 15 studies were curated and 1717 common interactors were uncovered among all these studies. KEGG analysis, Enrichr analysis, STRING interaction analysis was performed on these interactors. Therefore, we have identified novel host pathways that can be targeted for host-directed therapy against influenza in our review.